Harapan dan Kesiapan Menikah pada Dewasa Muda di Jakarta - Permatahati, Hilda Intan Budi; Rumondor, Pingkan C. B. (TAZKIYA Journal of Psychology, 2019)
This study is examined relationship between hope and marriage readiness on emerging adult who is engaged in Jakarta. The research method uses a quantitative approach. Subjects were 124 individuals aged 19-29 years who had become engaged and plan to get married, and lives in Jakarta. spearman rank correlation used to measure the degree of association between two variables. It was concluded, hope correlated with marriage readiness. Based on the marriage readiness aspects, hope has a positive correlation with six marriage readiness aspects: communication, financial management, child rearing, extended family background, religion, leisure time.